Presence of serum ferritin before and after bariatric surgery: Analysis in dentate and edentulous patients - Foratori, Gerson Aparecido; De Andrade, Francisco Juliherme Pires; Mosquim, Victor; Peres, Matheus De Carvalho Sales; Ceneviva, Reginaldo; Chaim, Elinton Adami; Peres, Silvia Helena De Carvalho Sales (Public Library of Science (PLoS), 2016)
Society has changed its own lifestyle, specially its eating habits and physical activities, leading to excessive weight and a sedentary behavior, which has contributed to obesity increase. Bariatric surgery is the most effective treatment to obesity, allowing weight loss and its maintenance. However, it has been related high levels of iron deficiency after surgery. A person's nutritional status might be affected by total or partial tooth loss. The aim of this longitudinal prospective cohort study was to evaluate the levels of serum ferritin before and after bariatric surgery and to identify if there is a relation with tooth loss. The sample was composed of 50 patients selected and assisted at Amaral Carvalho Hospital, located in Jaú city, Brazil. The use and necessity of prosthesis, dental absence or presence, and serum ferritin dosage were evaluated. Student's t test, Univariate analysis, Chi-square and Odds Ratio were adopted (p<0.05). There was no significant difference regarding the serum ferritin levels between dentate and edentulous patients prior to surgery (p = 0.436). After surgery, the serum ferritin levels were higher in edentulous patients (prosthesis users) when compared to the pre-surgical levels, and the post-surgical levels presented significant difference regarding the dentate patients (p = 0.024). It can be concluded that rehabilitated patients in postoperative period showed better levels of serum ferritin after surgical intervention.